A Guide for Local Benefit Sharing in Hydropower Projects - Wang, Chaogang (World Bank, Washington, DC, 2014)
Local benefit sharing in hydropower projects can be defined as the systematic efforts by project proponents to sustainably benefit local communities affected by hydropower investments. Benefit sharing is a promising approach for implementing hydropower projects sustainably, and is emerging as a supplement to the requirements of compensation and mitigation. Benefit sharing can provide equitable development, sustainability, and smooth project implementation for hydropower development. For benefit sharing mechanisms to work, the key enabling conditions are government policies, the legal and regulatory framework, corporate social responsibility strategies of development companies, and the capacity of local communities. Stakeholder engagement is essential in initiating and designing benefit sharing programs. This guide provides some advice to task teams on how to design effective local benefit sharing mechanisms in hydropower projects. Benefit sharing arrangements would ensure that local communities have the opportunity to benefit directly from hydropower development, which will make hydropower projects more environmentally and socially sustainable. As a long-term arrangement, benefit sharing can facilitate local development. It can respond to unexpected environmental circumstances in the operation of dams to ensure local communities receive adequate benefits. Arrangements for the equitable sharing of benefits can offer scope for local communities and all other stakeholders to avoid conflicts and focus on creating synergies to maximize local development opportunities.